Justice Sensitivity in Middle Childhood: A Replication and Extension of Findings - Bondü, Rebecca; Kleinfeldt, Maria (Frontiers in Psychology, 2021)
Previous research showed justice sensitivity (JS)—the tendency to perceive and negatively respond to injustice as a victim, observer, or perpetrator—to be reliably and validly measurable in middle childhood, but unexpected findings concerning mean values and measurement invariance require replication and re-test reliabilities, longitudinal relations with prosocial and aggressive behavior as well as relations with teacher-ratings are currently unknown. This study, therefore, examined mean values, factor structure, re-test reliabilities, and measurement invariance of self- and parent-rated JS as well as their relations with parent- and teacher-rated prosocial and aggressive behavior and a range of social skills in a sample of 1,329 children between 5 and 12 years of age (first measurement: M=8.05, SD=1.02, 51.1% girls). Using self- and parent-ratings, we could replicate the intended factor structure of three related, yet distinct JS subscales (victim, observer, perpetrator). We found strong measurement invariance between those ratings. Re-test reliabilities of parent-ratings were similar to older age-groups, but lower for self-ratings. All JS perspectives were positively related with Theory of Mind and empathy, indicating a good understanding of others’ internal states. Victim JS was negatively related to affective and behavioral self-regulation, observer and perpetrator JS showed positive relations. Victim JS negatively and observer and perpetrator JS positively predicted prosocial behavior. The opposite pattern was found regarding aggressive behavior. This study provides additional support that JS can be measured via self- and other-reports in childhood and that it may influence behavior early on. It adds to explaining the relations with prosocial and aggressive behavior.